A novel method to characterize thermal properties of the polymer and gas/supercritical fluid mixture using dielectric measurements. (December 2020) - Yao, Selina X.; Lee, Patrick C.; Park, Heon E.; Schadler, Linda S.
Abstract: Gases or supercritical fluids (SCF) are widely used in polymer science and engineering, as their dissolution into polymeric materials will alter their inherent thermal properties; including melting and crystallization temperatures ( T m and T c ). One possible method to determine these temperatures, at elevated pressures, is to use a high-pressure differential scanning calorimeter (HP-DSC). However, the elevated pressures used in HP-DSC may result in signal instabilities, limiting the testing window for these pressures. This study presents a novel testing system using dielectric measurements to determine the effects of dissolved gas/SCF on the T m and T c of polymers. We have developed an instrument to determine the dielectric properties of both polymer/gas and polymer/SCF mixtures, at elevated pressures and temperatures. Using the change in the measured dielectric constant or loss, T m and T c were determined. The effects of hydrostatic pressure and plasticization due to dissolved carbon dioxide (CO2 ) and Helium (He) on the T m and T c of high density polyethylene (HDPE) are presented and discussed. Both T m and T c increase with pressure and decrease due to plasticization, i.e ., pressure and plasticization are competing variables. The dissolution of He, having a low solubility into HDPE, reveals that pressure is the dominant effect. In contrast, the dissolution of CO2, having a high solubility into HDPE, shows that plasticization is predominant. Highlights: Developed a novel system for polymer dielectric property measurements at high temperatures and high pressures. Build the relationship between thermal property and dielectric property of the HDPE and gas/supercritical fluids mixture. Analyzed CO2 's plasticization and hydrostatic pressure effects on high density polyethylene.